Proceedings of the 5th EAI International Conference on Wireless Mobile Communication and Healthcare - "Transforming Healthcare 2015
DOI: 10.4108/eai.14-10-2015.2261688
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of design parameters for a reflection based long-term pulse oximetry sensor

Abstract: Pulse oximetry is a standard parameter for many years in clinical patient monitoring. There are also sensors that can be used at home. But all these sensors use the transmission based method to measure the oxygen saturation which require finger or ear clips that are uncomfortable and confining and therefore not fit for long-term monitoring. Sleep-related breathing disorders or breathing thin air in high altitudes can lead to insufficient oxygen intake. Insufficient oxygen supply can cause permanent damage to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Dresher and Mendelson (2006) concluded that SpO 2 and PR errors during motion artefact (induced by walking) were minimized at a contact pressure of 12 KPa. We used a sensor with a sensor area of 0.42 cm 2 , so a contact force of 0.5 N corresponds to a contact pressure of 12 KPa which agrees with the findings of Dresher and Mendelson (2006), while Bideaux et al (2015) concluded that a contact force of 15 mmHg (2 KPa or 0.2 N cm −2 ) and motion artefacts were hard to handle in a wristbased commercial product. Our results showed that a contact force of 0.5 N used with our sensor would be ideal for a forehead sensor.…”
Section: Discussion Of Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Dresher and Mendelson (2006) concluded that SpO 2 and PR errors during motion artefact (induced by walking) were minimized at a contact pressure of 12 KPa. We used a sensor with a sensor area of 0.42 cm 2 , so a contact force of 0.5 N corresponds to a contact pressure of 12 KPa which agrees with the findings of Dresher and Mendelson (2006), while Bideaux et al (2015) concluded that a contact force of 15 mmHg (2 KPa or 0.2 N cm −2 ) and motion artefacts were hard to handle in a wristbased commercial product. Our results showed that a contact force of 0.5 N used with our sensor would be ideal for a forehead sensor.…”
Section: Discussion Of Resultssupporting
confidence: 65%
“…Due to the interdependencies of one or several of these variables with each other, these approaches may have resulted in suboptimal solutions to minimize the effects of motion artefact during signal acquisition. Bideaux et al (2015) investigated the AC/DC ratio and signaltonoise ratio of reflectiontype pulse oximeter sensors on the wrist using different design parameters such as contact pressure and the distance between the pho todiode and the red and infrared LEDs. Bideaux et al concluded that constraints related to a minimum contact pressure of 15 mmHg (or 0.2 N cm −2 ) and motion artefacts were major impediments in the creation of a com mercial product.…”
Section: Current Methods For Mitigating Motion Artefact Based On Sing...mentioning
confidence: 99%
See 1 more Smart Citation
“…The reflective sensor can be applied to other parts of body, such as forehead or wrist. Therefore, the reflective PPG sensor is more suitable for the long-term and wearable measurement of physiological signals [3].…”
Section: Introductionmentioning
confidence: 99%